A Reaction‐Based Fluorescent Probe for Imaging of Native Hypochlorous Acid. Issue 21 (10th October 2019) - Wang, Jiamin; Men, Yuhui; Niu, Linqiang; Luo, Yang; Zhang, Jian; Zhao, Weili; Wang, Jianhong
Abstract: Hypochlorous acid (HOCl), one of the reactive oxygen species (ROS), is highly reactive and short‐lived. It is a challenge to dynamic monitor HOCl activity in living systems. Hence, we synthesized a new fluoresce nt probe RF1 based on protection of the hydroxyl group by N, N ‐dimethylthiocarbamate recognition group, which reached a low fluorescence background signal and highly sensitive property. On account of the electrophilic addition of Cl + to the sulfide of thiocarbamate moiety, probe RF1 was converted to resorufin and triggered emitting bright. RF1 showed not only the highly sensitive and selective response to HOCl in vitro, but also can be applied in environmental water samples and detected HOCl by test strips. Besides, the ability of RF1 monitoring HOCl in HeLa cells by exogenous simulation and tracing native HOCl in macrophages cells were also explored. Abstract : On account of the electrophilic addition of Cl + to the sulfide of thiocarbamate moiety, probe RF1 can be effectively activated by HOCl not only in vitro, but also in environmental water samples and test strips. More importantly, probe RF1 could track native HOCl in living RAW 264.7 cells. Therefore, RF1 may be a powerful tool for detecting HOCl in environmental samples and complicated living systems.